KONTRIBUSI PENGEMBANGAN EKOWISATA TAMAN SARI BUWANA TERHADAP BANJAR BENG KAJA, DESA TUNJUK, KABUPATEN TABANAN - I Wayan Sudinata; I Putu Budiarta (Soshum: Jurnal Sosial dan Humaniora, 2013)
The increase of world’s awareness on the importance of environmental protection and saturation towards conventional tourism activity which caused negative impact on the socio-cultural and environment has resulted changes in trend from conventional into alternative tourism. Taman Sari Buwana is one of the ecotourism in Bali which is developed in order to accommodate such trend. This study aims to know the contribution of Taman Sari Buwana Ecotourism development at Banjar beng Kaja, Tunjuk Village, Tabanan Regency. The sampling technique of this study used purposive and accidental sampling. Data is collected using questionnaires, direct observation, depth interview, Focus Group Discussion (FGD) and documentation. Data analysis used qualitative descriptive analysis. The results of this study shows that the development of ecotourism at Banjar Beng Kaja gives a positive contributions to economy, social and environment of Banjar Beng Kaja. They are to organization or group involved in the ecotourism, Elementary School No. 3 Tunjuk, Subak Kaliasem (local farmer’s organization), artist’s group, Banjar Pakraman Beng Kaja and Tunjuk Village. It is also contributing to the preservation of culture and environment of Banjar Beng Kaja. In order to ensure tourist satisfaction, it is necessary to improve some tourist facilities in there. Taman Sari Buwana Ecotourism need to cooperate with the Government of Tabanan Regency through the Departement of Tourism and and Public Works, especially in improving the road to Banjar Beng Kaja.